(3GdEaUGM aj EKHGJ EeGeI ehdGfG CejQ GdeDefjf Ydjg GdSdGes - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B...(3hGdZQV ajeG fhQOg GdBf HeYhfI Gddg YR hLd HYO GdPj PcQfGg hhUafG MGdg hHjfGg JdNjU LfS eaQO de jJefi HGdJMOjO ajeG CSdafGg hdG hLOfGg (B...s
(3BNQgG (B:s
... (3ef BjGJ GdbQif GdeMceGJ hGdGNHGQ GdUGObI HMLL GdJhGJQ hGdbQBf ef GdHjfGJ cJGHG CTjY ajg eYGfj GdcdGe djfVGa Edi gPG GdcJGH hJced Hg GdahGFO aj gPg GdCHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3GdCYdGe (B7\21s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds